Study of the incidence of Exequatur in divorce processes within the Ecuadorian Procedural System, period 2018 – 2019 - Gonzabay Flores, Jorge Luis (Revista Universidad de Guayaquil, 2022)
The present work aims to analyze the procedural system of homologations of international sentences and their application within the Ecuadorian territory, based on the theory of institutionalism and during the period 2018 – 2019, to determine the incidence of these. The purpose of the developed article is both explanatory and propositional, therefore, the formal and procedural requirements are studied; as well as the legal-normative figures protected in the current Ecuadorian legislation and in the international treaties of which Ecuador is a party are also analyzed. In addition, it is intended to show the importance of the correct analysis of the documentation and the spatial and jurisdictional competence, mainly of those who must know the cause according to the profuse circumstantial variables. For this purpose, it is necessary to study the general international doctrines on procedural matters and the invocation of the legal institution of “res judicata”.
Keywords: homologation; institutionalism; res judicata; legal-normative